Texturization of mono-crystalline silicon solar cells in TMAH without the addition of surfactant - 欧伟英 张瑶 李海玲 赵雷 周春兰 刁宏伟 刘敏 鲁伟明 张俊 王文静 (Journal of semiconductors, 2010)
Etching was performed on （100） silicon wafers using silicon-dissolved tetramethylammonium hydroxide （TMAH） solutions without the addition of surfactant. Experiments were carried out in different TMAH concentrations at different temperatures for different etching times. The surface phenomena, etching rates, surface morphology and surface reflectance were analyzed. Experimental results show that the resulting surface covered with uniform pyramids can be realized with a small change in etching rates during the etching process. The etching mechanism is explained based on the experimental results and the theoretical considerations. It is suggested that all the components in the TMAH solutions play important roles in the etching process. Moreover, TMA^＋ ions may increase the wettability of the textured surface. A good textured surface can be obtained in conditions where the absorption of OH-/H2O is in equilibrium with that of TMA＋/SiO2（OH）2^-.